Trial Advocacy and Nitojutsu - Chris Dent (Legal Education Review)
Miyamoto Musashi was a master Japanese swordsman. His text, the Book of Five Rings, sets out his philosophy on combat and the way of the warrior. This article takes his teachings and applies them to art of trial advocacy. The Five Scrolls of Musashi’s text allow for an engagement with the fundamental importance of preparation, the effective deployment of law and fact, awareness and professional ethics. The connections are made through the use of current experts in advocacy, including Glissan and Hampel. The use of techniques involving katana is, of course, only a metaphor – one aimed at getting law students to think of trials in a more life-or-death way. Advocacy is not the showiness of TV, but the hard grind of training and preparation that was the life of a ronin.